Washington's dark secret : the real truth about terrorism and Islamic extremism - Maszka, John, 1963- (Potomac Books, an imprint of the University of Nebraska Press, 2018)
"Much of the violence that is touted as terrorism today is not terrorism at all. Maszka delves into the repercussions of a government that capitalizes on an "us vs. them" mentality, rather than focusing on the real reason behind the war on terror--natural resources."--